2006
DOI: 10.1088/0264-9381/23/18/009
|View full text |Cite
|
Sign up to set email alerts
|

Black holes in Einstein-aether theory

Abstract: We study black hole solutions in general relativity coupled to a unit timelike vector field dubbed the "aether". To be causally isolated a black hole interior must trap matter fields as well as all aether and metric modes. The theory possesses spin-0, spin-1, and spin-2 modes whose speeds depend on four coupling coefficients. We find that the full three-parameter family of local spherically symmetric static solutions is always regular at a metric horizon, but only a two-parameter subset is regular at a spin-0 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
324
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(346 citation statements)
references
References 18 publications
17
324
3
2
Order By: Relevance
“…Additional tests of ae-theory can come from the study of stellar solutions and black holes, begun in [15,16], and from the "ultimate" test [7] provided by observations of binary pulsar systems. This work begins that examination with a calculation of the generation of gravityaether radiation by a nearly Newtonian source and the subsequent energy loss, or radiation damping, of the source.…”
Section: Introductionmentioning
confidence: 99%
“…Additional tests of ae-theory can come from the study of stellar solutions and black holes, begun in [15,16], and from the "ultimate" test [7] provided by observations of binary pulsar systems. This work begins that examination with a calculation of the generation of gravityaether radiation by a nearly Newtonian source and the subsequent energy loss, or radiation damping, of the source.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to investigate neutron stars or black holes. In Einstein-Aether theory, these features are investigated and show interesting differences from the case in general relativity [18,19,20]. As for TeVeS, black holes have been investigated only for the cases where the scalar field diverges at the horizon [8,13] or the scalar field is constant [16].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We notice that τ αβ disappears to O(1). From (3.1), we obtain 19) to O(2). Thus, this term also disappears to O(1).…”
Section: Calculation Of Ppn Parametersmentioning
confidence: 99%
“…Einstein-aether theory contains four free parameters, c 1 , c 2 , c 3 and c 4 representing coefficients of different terms in the action. In [6] black hole solutions were found for certain ranges of the parameters; however, it was found that when c 1 was sufficiently large the method did not find black hole solutions.…”
Section: Introductionmentioning
confidence: 96%
“…For Einstein-aether theory, both of these approaches have been used. [6][7][8] The approach of [6] was to assume a static, spherically symmetric spacetime with an event horizon. These assumptions reduced the field equations of the theory to a set of coupled ordinary differential equations (for the fields as a function of the radial coordinate) which satisfied an appropriate set of boundary conditions (smoothness at the horizon and asymptotic flatness at infinity).…”
Section: Introductionmentioning
confidence: 99%